2013 Fourth International Conference on E-Learning "Best Practices in Management, Design and Development of E-Courses: Standard 2013
DOI: 10.1109/econf.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hindrances to the Utilization of e-Learning System in Architectural Courses

Abstract: the core of Architectural education is the design studio where -face to face-social interaction, negotiations and communications happen between tutors and students. These communications are essential for development of the design concept and initiation of student's creativity. Laboratory and theoretical courses are considered as backup or supportive to the design studio's education. At the University of Dammam, an ambitious e-learning system plan was initiated and the system was gradually installed during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Consequently, it is necessary that lecturers should be trained not only to use e-learning applications to teach theoretical courses, but also to integrate them into their teaching practices in traditional design studio environments. Although the findings of some previous research studies have identified positive attitudes among members of university teaching staffs concerning the use of e-learning systems [36,39], some lecturers expressed concern about the ability of e-learning systems to meet the specific requirements of studio-based disciplines [40]. The findings that emerged from the data that the interviews and the document analysis generated revealed that while some of the interviewees were not in favour of teaching design and studio-based courses using the e-learning applications that were in use at CPUT at the time of the conducting of the study, others believed that it could be beneficial to use them to teach theoretical courses.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Consequently, it is necessary that lecturers should be trained not only to use e-learning applications to teach theoretical courses, but also to integrate them into their teaching practices in traditional design studio environments. Although the findings of some previous research studies have identified positive attitudes among members of university teaching staffs concerning the use of e-learning systems [36,39], some lecturers expressed concern about the ability of e-learning systems to meet the specific requirements of studio-based disciplines [40]. The findings that emerged from the data that the interviews and the document analysis generated revealed that while some of the interviewees were not in favour of teaching design and studio-based courses using the e-learning applications that were in use at CPUT at the time of the conducting of the study, others believed that it could be beneficial to use them to teach theoretical courses.…”
Section: Discussionmentioning
confidence: 89%
“…These factors have also been identified in previous studies by researchers, such as [34], who emphasises the necessity of providing robust infrastructure and advanced technical support to both members of faculty and students. Accordingly, it is imperative to design and develop innovative technology to permit synchronous communication and visualisation, specifically for studio-based teaching and learning environments [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through previous studies, it was noted that it is very important to plan for the first design decisions in which new architectural students made their first experiences (Ozorhon' et al, 2016). Not to mention that the study by Sidawi (2013), which was conducted in the period from 2010-2013 to students of the CAP, had indicated that the design studio environment is slowly improving, while it must be radically strengthened to help students produce creative projects. This prompted researchers to develop the teaching approach to Basic Design courses 1 and 2, and that is over more than a year to reach the best practices that support the design process and creativity for new students.…”
Section: Discussionmentioning
confidence: 99%